Transgenesis-mediated reproductive dysfunction and tumorigenesis: effects of immunological neutralization. - Ruchi Sachdeva; Neetu Bhardwaj; Ilpo Huhtaniemi; Usha Aggrawal; Swatantra Kumar Jain; Rana Zaidi; Om Singh; Rahul Pal (PLoS ONE, 2012)
Human chorionic gonadotropin (hCG) was initially thought to be made only during pregnancy, but is now known to also be synthesized by a variety of cancers and is associated with poor patient prognosis. Transgenic expression of βhCG in mice causes hyper-luteinized ovaries, a loss in estrous cyclicity and infertility, increased body weight, prolactinomas and mammary gland tumors. Strategies were devised to generate antibody responses against hCG to investigate whether reversal of the molecular processes driving tumorigenesis would follow. hCG-immunized transgenic mice did not exhibit increases in body weight or serum prolactin levels, and gross ovarian and pituitary morphology remained normal. While non-immunized transgenic animals demonstrated heightened levels of transcripts associated with pituitary tumorigenesis (HMG2A, E2F1, CCND1, PRL, GH, GAL, PTTG1, BMP4) and decreased levels of CDK inhibitors CDKN1B (p27), CDKN2A (p16) and CDKN2c (p18), immunization led to a reversal to levels found in non-transgenic animals. Serum derived from transgenic (but not non-transgenic) mice led to enhanced transcription as well as expression of VEGF, IL-8, KC (murine IL-8) and MMP-9 in tumor cells, effects not seen when sera derived from hCG-immunized transgenic mice was employed. As the definitive indication of the restoration of the reproductive axis, immunization led to the resumption of estrous cyclicity as well as fertility in transgenic mice. These results indicate that hCG may influence cancer pathogenesis and progression via several distinct mechanisms. Using a stringent in vivo system in which βhCG acts both a "self" antigen and a tumor-promoting moiety (putatively akin to the situation in humans), the data builds a case for anti-gonadotropin vaccination strategies in the treatment of gonadotropin-dependent or secreting malignancies that frequently acquire resistance to conventional therapy.